Global Factors and Emerging Market Spreads - Martín González Rozada; Eduardo Levy Yeyati (Inter-American Development Bank, Research Department, 2006)
This paper shows that a large fraction of the variability of emerging market bond spreads is explained by the evolution of global factors such as risk appetite (as reflected in the spread of high yield corporate bonds in developed markets), global liquidity (measured by the international interest rates) and contagion (from systemic events like the Russian default). This link has remained relatively stable over the history of the emerging market class, is robust to the inclusion of country-specific factors, and helps provide accurate long-run predictions. Overall, the results highlight the critical role played by exogenous factors in the evolution of the borrowing cost faced by emerging economies.
Keywords: 330; Länderrisiko; Unternehmensanleihe; Liquidität; Schwellenländer; Welt